Turkey’s Evolving Trade Integration into Pan-European Markets - Kaminski, Bartlomiej (World Bank, Washington, DC, 2012)
This is an empirical paper seeking to identify the mode of Turkey's integration into global markets in general, and pan-European markets in particular, as revealed in its trade performance. The analysis provides empirical support to the following observations. First, thanks to steady expansion of trade in goods and services since the mid-1980s, Turkey has become highly integrated into the world economy. Second, Turkey's export performance in 1996-2004 in EU markets bears strong similarities to the aggregate performance of new EU members from Central Europe (EU-8). Similarities include dynamics, similar factors responsible for the increased presence in EU markets, factor content, and the role of "producer-driven" network trade. Turkey, together with Hungary, the Czech Republic, the Slovak Republic, Slovenia, Estonia, and Poland, stands as one of the top performers in "producer-driven" network trade indicating participation in a new global division of labor based on production fragmentation. The available evidence suggests an economic success story in the making. Export expansion owes a lot to improved policy environment and domestic liberalization. It is rather telling that the recent expansion has coincided with the implementation of most of the provisions of the EU-Turkey Customs Union Agreement, the completion of the removal of tariffs on trade in industrial products among pan-European parties to the Pan European Cumulation of Origin Agreement, and improved macroeconomic stability after the 2001 crisis.